EFFECT OF AQUEOUS EXTRACT OF CRYPTOLEPIS SANGUINOLENTA ON PHARMACOKINETICS OF ARTESUNATE (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The aim of this study is to investigate the effect of aqueous extract of Cryptolepis sanguinolenta on the pharmacokinetics of the antimalarial; artesumate in male Sprague-Dawley rats. Reconstituted freeze dried Cryptolepis sanguinolenta was administered in drinking water at the therapeutic dose of 36 g/kg body weight for two (2) weeks, followed by a single oral dose of artesunate (150 mg/kg body weight). The Concentration - Time course; Maximum Whole Blood Concentration, Cmax; Time for the Maximum Concentration, Tmax; Bioavailability; Elimination Rate Constant; Half- life; Clearance; Volume of Distribution and Absorption Rate Constant were measured. Results indicated that about 80% of dihydroartemisinin was recovered during extraction suggesting that the extraction procedure was effective. The elimination rate constant and clearance of dihydroartemisinin the most potent metabolite of artesunate increased by 233.3% and 62.1% respectively in rats which received concurrent administration of Cryptolepis sanguinolenta compared to control (artesunate only). This resulted in significant decrease (p < 0.05) in the Bioavailability (40.1%), Volume of Distribution (68.1%) and Half-life (52.1%) of dihydroartemesinin. The findings therefore, showed that Cryptolepis sanguinolenta could cause sub-therapeutic blood levels of dihydroartemisinin of artesunate leading to decreased effectiveness and possibly drug resistance as a result of herb-drug interactions. Thus, in clinical practice, patients should be advised on the serious implication of using Cryptolepis sanguinolenta and artesunate together.